Progress in the Use of Induced Pluripotent Stem Cell-Derived Neural Cells for Traumatic Spinal Cord Injuries in Animal Populations: Meta-Analysis and Review. (22nd March 2019) - Ramotowski, Christina; Qu, Xianggui; Villa-Diaz, Luis G.
Abstract : Induced pluripotent stem cells (iPSCs) are cells genetically reprogrammed from somatic cells, which can be differentiated into neurological lineages with the aim to replace or assist damaged neurons in the treatment of spinal cord injuries (SCIs) caused by physical trauma. Here, we review studies addressing the functional use of iPSC-derived neural cells in SCIs and perform a meta-analysis to determine if significant motor improvement is restored after treatment with iPSC-derived neural cells compared with treatments using embryonic stem cell (ESC)-derived counterpart cells and control treatments. Overall, based on locomotion scales in rodents and monkeys, our meta-analysis indicates a therapeutic benefit for SCI treatment using neural cells derived from either iPSCs or ESCs, being this of importance due to existing ethical and immunological complications using ESCs. Results from these studies are evidence of the successes and limitations of iPSC-derived neural cells in the recovery of motor capacity. Stem Cells Translational Medicine 2019;8:681&693 : Abstract : Traumatic spinal cord injuries can lead to impairment of motor movement, and iPSCs-derived neural cells can be used for treatment as indicated in the left side of the illustration. Here, we review studies using this cell transplantation treatment in rodent models, as shown in the right side of the illustration, with the goal to evaluate its effectiveness for motor recovery.